Uptake of moss‐derived human recombinant GAA in Gaa−/− mice. Issue 1 (1st February 2021) - Hintze, Stefan; Dabrowska‐Schlepp, Paulina; Berg, Birgit; Graupner, Alexandra; Busch, Andreas; Schaaf, Andreas; Schoser, Benedikt; Meinke, Peter
Abstract: Pompe disease, an autosomal recessive lysosomal storage disorder, is caused by deficiency of lysosomal acid alpha‐glucosidase (GAA). On cellular level, there is lysosomal‐bound and free accumulation of glycogen and subsequent damage of organelles and organs. The most severe affected tissues are skeletal muscles and heart. The only available treatment to date is an enzyme replacement therapy (ERT) with alglucosidase alfa, a recombinant human GAA (rhGAA) modified with mannose‐6‐phosphate (M6P), which is internalized via M6P‐mediated endocytosis. There is an unmet need to improve this type of therapy, especially in regard to skeletal muscle. Using different tissue culture models, we recently provided evidence that a moss‐derived nonphosphorylated rhGAA (moss‐GAA), carrying a glycosylation with terminal N ‐acetylglucosamine residues (GnGn), might have the potential to improve targeting of skeletal muscle. Now, we present a pilot treatment of Gaa −/− mice with moss‐GAA. We investigated general effects as well as the uptake into different organs following short‐term treatment. Our results do confirm that moss‐GAA reaches the target disease organs and thus might have the potential to be an alternative or complementary ERT to the existing one.